Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fpsyg.2020.595713
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer and Resilience: The Controversial Role of Perceived Emotional Intelligence

Abstract: Cancer is a chronic disease that causes the most deaths in the world, being a public health problem nowadays. Even though breast cancer affects the daily lives of patients, many women become resilient after the disease, decreasing the impact of the diagnosis. Based on a positive psychology approach, the concept of co-vitality arises understood as a set of socio-emotional competencies that enhance psychological adaptation. In this sense, emotional intelligence is one of the main protective factors associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(62 citation statements)
references
References 39 publications
7
39
1
Order By: Relevance
“…Acceptance of the disease is assessed relatively highly by women with breast cancer who have had mastectomy. These patients obtained the result of M = 28.60 (SD = 8.47) in the AIS test [30].…”
Section: Discussionmentioning
confidence: 87%
“…Acceptance of the disease is assessed relatively highly by women with breast cancer who have had mastectomy. These patients obtained the result of M = 28.60 (SD = 8.47) in the AIS test [30].…”
Section: Discussionmentioning
confidence: 87%
“…Cancer survivors report being aware of how precarious life is, while also feeling the joy of being alive [ 55 ]. Similarly, they have been found to be more resilient and better able to repair their mood than healthy women [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies showed that patients with BC have high anxiety and depression levels and the anxiety was associated with physical burdens (Park et al, 2018), women patients with BC were shown to have higher resilience and mood repair levels than women with non-BC (Guil et al, 2020). However, more pain, fatigue, and decreased body image were associated with decreased quality of life of women with BC (McClelland et al, 2015).…”
Section: Introductionmentioning
confidence: 96%